Meningkatkan Keterampilan Kreatif Siswa Sekolah Dasar Negeri 060930 Medan - Harefa, Rizka Fadhilah Zahra; Lubis, Mia Aulina; Ritonga, Fajar Utama (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2023)
This article aims to discuss efforts to improve the creative skills of 060930 Medan Elementary School students. This research was conducted at 060930 Medan State Elementary School which is located at Jl. Karya Jaya No. 52, Pangkalan Masyhur, Medan Johor District, Medan City, North Sumatra. Thinking skills are one of the skills that must be possessed by elementary school students. Collecting data in this study was by conducting interviews, observing through observation sheets on students' creative thinking skills, teacher activity sheets in carrying out learning. The results of this study are 1) there is a need for a specially designed learning to improve students' creative thinking abilities, 2) teachers need to provide learning resources in the form of modules, 3) the need for collaboration between students, teachers and parents in order to achieve optimal educational goals.